Dysplasia Epiphysealis Hemimelica of the Talus: Two Case Reports - SK Bhosale; DB Dholakia; BA Sheth; SK Srivastava (Journal of Orthopaedic Surgery, 2005)
Trevor's disease, also known as dysplasia epiphysealis hemimelica, is an uncommon skeletal developmental disorder representing an osteochondroma occurring in one or more epiphyses. We present 2 cases of dysplasia epiphysealis hemimelica in an 8-year-old female and a 12-year-old male who suffered from a hard swelling of the ankle joint. The female patient was treated by surgical excision and the male patient conservatively.